Clarifications regarding Noël Necker’s names associated to Chaptalia (Asteraceae: Mutisieae) - Katinas, Liliana (2017)
The generic name Chaptalia was founded by Ventenant in 1802. In 1891 Kuntze transferred 19 species from Chaptalia to Thyrsanthema, a name established by Necker in 1790, on the basis that Thyrsanthema had priority over the name Chaptalia. The monomial system of nomenclature used by Necker in his Elementa Botanica published in 1790, together with a confusing typification on the basis of Linnean species, led to different interpretations of Necker’s changes by botanists. In 1905 the Vienna Code considered Chaptalia as a nomen conservandum and Thyrsanthema as a nomen rejiciendum. In 1959, the Montreal Code established that the ‘species naturales’ of Necker are not to be treated as generic names. As a consequence, the name Chaptalia was considered a case of superfluous conservation, because Kuntze did not validate Thyrsanthema until 1891. Edward Greene in 1906 added another point of controversy establishing that the names Chaptalia and Thyrsanthema referred to totally different taxa. The nomenclatural history of Chaptalia and allied names described by Necker (Atasites, Petasites, Thyrsanthema and Tussilago) is reviewed, and the current status of these names is presented.